Evaluasi Kinerja Bank dalam Penyaluran Kredit Kepada Usaha Kecil Dan Menengah (UKM) - Irfan Ridha; isma Dwiyanti; Riza Febdillah; Rizandy Marsya; Syirad Syirad; Tika Tika; Uli Widiriyani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Small and Medium Enterprises (SMEs) play a crucial role in a country's economic growth. Therefore, lending to SMEs is an important element in supporting this sector. This study aims to evaluate bank performance in lending to SMEs, with a focus on efficiency, security and economic impact. This research methodology involves analyzing historical data from a number of banks that are active in supporting SMEs. Data includes the volume of credit disbursed, the interest rate applied, the credit approval process, and the non-performing loan ratio. Apart from that, the economic impact of credit provided to SMEs is also evaluated through business growth, job creation, and contribution to local GDP. The research results show variations in bank performance in lending to SMEs. Certain banks achieve high levels of efficiency in the credit approval and monitoring process, while others may face challenges in managing credit risk. The economic impact of credit to SMEs is positive, with significant business growth and job creation having a positive impact on the local economy.